Candida Vulvovaginitis in pregnancy. - Yousif, Eman E.; Hussien, Sawsan A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Vulvovaginal candiddiasis is an opportunistic mucosal infection caused by Candida albicans that affects large number of otherwise healthy women of child bearing age. Acute episodes often occur during pregnancy.Patients and methods: This study was done on 50 pregnant women with Candida vulvovagnitis who were diagnosed by direct microscopic examination, culture technique, germ tube production, chlamydospore, and Api 20 candida system, at Baghdad Teaching Hospital in the period between October 2008 to February 2009.Results: The study group included 50 pregnant women with Candida vulvovaginitis . The percentage of pregnant women with Candida albicans infection who their age is higher than 30 years old is 100 %( 23cases), while the percentage is high as 100 % (36cases) in pregnant women whom their gestational age more than 37 week gestation. On the other hand the percentage of pregnant women who have children more than 3 (100%) (12cases). Candida albicans was occurred more frequently when pregnant women suffered from diabetes mellitus 100 %( 14cases).Conclusion: Direct relationship was detected between the percentage of infection and the age of the mother, gestational age, parity, and the presence of diabetes mellitus, the higher the age of the mother, gestational age, parity, and the presence of diabetes mellitus, the higher percentage of infection with Candida albicans during pregnancy.